Climate services user needs assessment - Mekong River Delta, Vietnam - Van, Lam Luong; Nguyen, Cong Thanh; Giles, James; Le, Tam Thi; Swaans, Cornelis (2024)
This report presents the results of a study assessing the climate services needs among smallholder farmers in the Mekong River Delta, Vietnam. It includes discussions on the analysis of respondent and household data, priority farming systems, key agricultural decisions, current/desired use of (D)CAS+, and digital readiness. Throughout the study, special attention was given on the role of farmers in decision making and on gender. Findings from this study can help assess potential challenges and opportunities for DCAS+ and inform policy and practices around the design, development, and scaling based on farmer needs.